15th World Congress of Psychophysiology - Glăveanu, Vlad (Europe’s Journal of Psychology, 2010)
Budapest, Hungary August 30 – September 4, 2010 Following the high standards set by the International Organization of Psychophysiology, the Program of this 15th World Congress of Psychophysiology will be composed of Invited Keynote Presentations, Symposia and Poster Sessions on the most advanced findings on all aspects, branches and areas of Psychophysiology as a leading Neuroscience (see Main Topics of the World Congress). All accepted abstracts will be published in the International Journal of Psychophysiology which will be distributed to all registered Delegates at the World Congress site in Budapest.